Origin of the brachial plexus nerves of the white-tailed deer (Odocoileus virginianus) in comparison with other ruminants - Vélez García, Juan Fernando (2018)
The objective of this study was to identify the spinal nerves that give origin to the brachial plexus and the origin of each of the nerves of the white-tailed deer (Odocoileus virginianus), as well as to compare the results with those reported in the literature for other ruminants. The two brachial plexuses of four specimens (three females and one male) were dissected. The brachial plexus was originated by contribution of the roots of the ventral branches of the spinal nerves from C6 to T1 (3/4), and from C6 to T2 (1/4). From these originated the suprascapular, subscapular, axillary, radial, ulnar, median, thoracodorsal, musculocutaneous, cranial pectoral, pectoral caudal, long thoracic, lateral thoracic, subclavian, and dorsal scapular nerves. The origin of the brachial plexus of O. virginianus was more similar to that reported in cattle. The formation of the nerves presents similarities and variants with what has been reported in other ruminants. Likewise, there may be interspecific, intraspecific anatomical variations, and even in the collateral plexuses of the same specimen for the origin of the nerves.